Ketepatan ultrasonografi dan mammografi dalam mendiagnosis wanita dengan kanker payudara di RSUP Sanglah Denpasar - Cokorda Agung Abi Baruna; I. B Tjakra Wibawa Manuaba (Intisari Sains Medis, 2019)
Introduction: The high incidence of breast cancer in women, accompanied by delays in making contact with medical personnel and the absence of good early detection contribute to the very high mortality caused by breast cancer. Early detection using ultrasound and mammographic modalities plays an important role in the early diagnosis of breast cancer which will have an impact on the survival of patients. This study aims to compare the diagnostic values of ultrasonography and mammography compared with histopathological features in patients with breast cancer.Methods: This study used a diagnostic test design with a retrospective approach that compared sensitivity values, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratio from mammography and ultrasonography to histopathological morphology in patients with breast cancer at Sanglah General Hospital Denpasar .Results: It can be seen that in the total sample, ultrasonography in the toal condition of the sample has a diagnostic value that is very similar to mammography in establishing a diagnosis of breast cancer. Whereas at the age of> 40 years mammography has a diagnostic test value that is far better than ultrasonography (sensitivity: 85.71; specificity: 83.33; PPV: 92.30; NPV: 76.92; LLR (+): 5, 14; LLR (-): 0.17).Conclusion: ultrasonography and mammography have almost the same precision in the whole sample, but mammography has a better diagnostic value compared to ultrasonography in people aged> 40 years.